2004
DOI: 10.1093/occmed/kqh102
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and cardiovascular function at rest and during exercise testing in a healthy working population: effects of outdoor traffic air pollution

Abstract: The findings suggest that chronic occupational exposure to urban pollutants reduces resistance to physical effort and increases the risk of cardiovascular and respiratory changes including slight hypoxemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 38 publications
1
33
1
3
Order By: Relevance
“…8 When compared with other studies conducted on traffic policemen by Thippanna G. and Lakhtakia, Volpino et al and Karita et al it was observed that 37% to 43% traffic policemen were current smokers, which was more than that observed in the present study (7.02%). [16][17][18] In the study carried out by Charles et al it was observed that 12.9% male police officers were current smokers and 79.4% male police officers were used to take alcohol. 19 In the study carried out by Shabana et al it was found that 22.6% policemen had habit of smoking, 8.5% policemen had habit of tobacco chewing and 31.1% policemen had habit of alcohol intake.…”
Section: 32%mentioning
confidence: 99%
See 1 more Smart Citation
“…8 When compared with other studies conducted on traffic policemen by Thippanna G. and Lakhtakia, Volpino et al and Karita et al it was observed that 37% to 43% traffic policemen were current smokers, which was more than that observed in the present study (7.02%). [16][17][18] In the study carried out by Charles et al it was observed that 12.9% male police officers were current smokers and 79.4% male police officers were used to take alcohol. 19 In the study carried out by Shabana et al it was found that 22.6% policemen had habit of smoking, 8.5% policemen had habit of tobacco chewing and 31.1% policemen had habit of alcohol intake.…”
Section: 32%mentioning
confidence: 99%
“…In the present study 29.82% traffic policemen were found with hypertension which was more than that observed in 16% and 25% traffic policemen in the studies carried out by Volpino et al and Satapathy respectively. 17,26 The URTI was observed in 17 (14.91%) traffic policemen. Chronic rhinitis was found in 14.04% traffic policemen.…”
mentioning
confidence: 97%
“…Systolic and diastolic blood pressure, evaluated in eight studies (12,13,(28)(29)(30)(31)(32)(33), and heart rate, in two studies (31,34), show no statistically significant differences in the exposed compared to controls. The studies were heterogeneous between them.…”
Section: Results Of Continuous Variables: Class Imentioning
confidence: 98%
“…Even if the process implying this connection is not yet fully explained, it is possible to recognize some risk factors, such as the exposition to chemical agents shortterm (2,(8)(9)(10)(11) and long-term (2,5,(12)(13)(14)(15) exposition to particulate matter, lead (16)(17)(18)(19)(20)(21), cadmium (4), carbon monoxide (22) and to traffic noise (12,13,23,24). The aim of this meta-analysis is to conduct a systematic revision of the scientific evidence on cardiovascular effects in workers exposed to urban pollution (25).…”
mentioning
confidence: 99%
“…Innymi ocenianymi parametrami są np. : zużycie tlenu (oxygen uptake -VO 2 ), eliminacja dwutlenku węgla (CO 2 production -VCO 2 ), zuży-cie tlenu na progu anaerobowym (oxygen uptake on anaerobic treshold -VO 2 AT) oraz wielkość wentylacji (ventilation -VE) (3). Niektóre z nich są używane do oceny rokowania pacjentów z niewydolnością serca i mogą być pomocne w kwalifikacji chorych do przeszczepu serca.…”
Section: Wstępunclassified